Squalene-producing thraustochytrids isolated from mangrove habitats in the Sidoarjo District, Indonesia, and the antioxidant activity of the isolated strain (Biodiversitas Journal of Biological Diversity, 2025)
Abstract. Arifin NB, Fakhri M, Yuniarti A, Musa M, Hariati AM. 2025. Squalene-producing thraustochytrids isolated from mangrove habitats in the Sidoarjo District, Indonesia, and the antioxidant activity of the isolated strain. Biodiversitas 26: 1975-1982. Squalene, a polyunsaturated triterpenic hydrocarbon, is commonly used in the pharmaceutical, cosmetic, and nutraceutical industries because of its antioxidant and anti-inflammatory properties; however, traditional sources such as deep-sea shark liver oil and plant-based alternatives such as the olive Olea europaea present sustainability challenges. This study aimed to isolate and characterize squalene-producing thraustochytrids from mangrove habitats in Sidoarjo, Indonesia, and evaluate their potential antioxidant activity. Isolation was performed from fallen mangrove leaves and was identified based on morphological and molecular analysis using 18S rRNA sequencing. The lipid and squalene contents were quantified through solvent extraction and high-performance liquid chromatography, whereas the antioxidant activity was assessed using the DPPH radical scavenging assay. A total of 14 strains were successfully isolated, which showed cell morphologies including circular and/or ameboid-like shapes and the presence of tetrad cell division. Molecular analysis showed that all isolates were close to the genus Aurantiochytrium. Seven of the isolated strains exhibited high lipid contents (>35% of dry cell weight). Among these strains, AB12 produced the highest lipid content (54.77%), whereas AB14 exhibited the highest squalene yield (2.18 mg g?1 dry cell weight). Antioxidant analysis revealed that lipid extracts from AB12 displayed significant radical scavenging activity, outperforming pure squalene, thereby indicating potential synergistic effects with other bioactive compounds. These Indonesian mangrove-derived isolates represent a promising alternative for sustainable squalene production, addressing the limitations of conventional sources. This study provides novel insights into squalene-producing Aurantiochytrium strains from Indonesian mangrove forests.
Keywords: Antioxidant activity, Aurantiochytrium, mangrove, squalene, thraustochytrids